Physical and material aspects in using visible laser pulses of nanosecond duration for ablation - Körner, Carolin; Mayerhofer, Roland; Hartmann, Mark; Bergmann, Hans Wilhelm (Applied Physics A-Materials Science & Processing, 1996)
Interaction phenomena of 50 ns copper vapour laser pulses (λ = 511/578 nm) with matter are investigated. The basic ablation process is classified into four fundamental classes. On basis of this classification processing results are connected with specific material properties like the brittleness, the viscosity of the melt or the optical properties. Knowing these properties a prognosis of the expected fundamental process is possible. In order to generate a geometrically defined structure via ablation in a given material-specific process, strategies have to be developed. Typical examples for process strategies are given.